Scorecard for Subsidies : How Utility Subsidies Perform in Transition Economies - Lovei, Laszlo; Gurenko, Eugene; Haney, Michael; O'Keefe, Philip; Shkaratan, Maria (World Bank, Washington, DC, 2012)
Unlike the poor in many developing countries, those in Central and Eastern Europe, and the former Soviet Union, are highly connected to network utilities. During the early 1990s, it became clear that without subsidies, many households would have difficulty paying their utility bills. Governments started to experiment with various subsidy schemes. This note describes the main schemes, scoring those, based on the following criteria: the extent to which the poor are being reached, i.e., coverage; the share of the subsidy that goes to the poor, i.e., targeting; predictability of the benefit for the poor; the extent of pricing distortions, and other unintended side-effects; and, administration costs, and difficulty. Moreover, the note provides a methodology for governments designing subsidies, to decide which scheme is likely to be the best for their country.